2007
DOI: 10.1063/1.2812699
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of thermal conductivity in magnetite based nanofluid due to chainlike structures

Abstract: We observe a dramatic enhancement of thermal conductivity in a nanofluid containing magnetite particles of average diameter of 6.7nm under the influence of an applied magnetic field. The maximum enhancement in the thermal conductivity observed is 300% (k∕kf=4.0) at a particle loading of 6.3vol%. The increase in thermal conductivity is attributed to the effective conduction of heat through the chainlike structures formed in the nanofluid. This finding is consistent with the theoretical prediction of enhanced th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
171
1
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 355 publications
(181 citation statements)
references
References 20 publications
7
171
1
2
Order By: Relevance
“…As for instance, recent experimental results have shown an anomalous thermal conductivity enhancement by introducing very small amounts of copper nanoparticles, carbon nanotubes, magnetite nanoparticles, among other colloidal particles in the liquid carriers. [1][2][3][4][5][6][7] In addition, enhanced ignition properties has been found on fuels containing aluminum nanoparticles. 5 Besides better heat transfer properties nanoparticles also act as catalysts and can help on the reduction in pollutant production.…”
Section: Introductionmentioning
confidence: 99%
“…As for instance, recent experimental results have shown an anomalous thermal conductivity enhancement by introducing very small amounts of copper nanoparticles, carbon nanotubes, magnetite nanoparticles, among other colloidal particles in the liquid carriers. [1][2][3][4][5][6][7] In addition, enhanced ignition properties has been found on fuels containing aluminum nanoparticles. 5 Besides better heat transfer properties nanoparticles also act as catalysts and can help on the reduction in pollutant production.…”
Section: Introductionmentioning
confidence: 99%
“…Brownian motion and aggregation which improves the thermal transport were claimed to be the reasons of enhanced thermal conductivity of these nanofluid systems. [22][23][24] Thermal conductivities of magnetic nanofluids composed of iron oxide nanoparticles dispersed in various base fluids have been investigated experimentally and the results showed that the thermal conductivity linearly increases with increasing particle concentration, but also depends on the method of preparation and the base fluid used. 19,25 However, there are contradictory results showing enhancement both with increasing 16,19 and decreasing particle size.…”
Section: Introductionmentioning
confidence: 99%
“…14 The clustering hypothesis expands the range of thermal conductivities that are acceptable within the classical view, but this fact alone does not prove that clustering is indeed the mechanism responsible for enhancements that fall in this range. In fact, the aggregation state of the colloid was not controlled in the studies reviewed by Eapen et al 14 The most direct evidence for the thermal effect of aggregated structures comes from dispersions of magnetic nanoparticles, 16,17 where it has been demonstrated that the conductivity of the dispersion increases monotonically with the applied magnetic field, due to the formation of linear chains along the magnetic lines. Linear chains, however, are not typical in usual colloidal systems, whose clusters tend to form fractal structures with fractal dimension in the range 1.8-2.5.…”
mentioning
confidence: 99%
“…The results follow qualitative trends that have been reported previously. 16,17,19 We now examine this behavior in quantitative terms, in the context of Maxwell's theory, by replotting the data as a function of the volume fraction of the primary particles as shown in Fig. 3.…”
mentioning
confidence: 99%